Numerical methods in understanding reaction pathways NOx oxidation - Jaroszyńska-Wolińska, Justyna; Malinowski, Szymon (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Different quantum chemical models were applied in energetic analysis of process of oxidation of NO and NO2 through reaction with ozone generated by non-thermal equilibrium (low temperature), atmospheric pressure plasma. The potential energy surfaces of systems comprising NO and NO2 with ozone were characterized. The NOx oxidation processes well known, at the molecular level, were modelled by ab initio quantum methods to calculate the total reaction energy, Et, of each step in the reaction chain. Chemistry was further applied in an attempt to detect the presence of any transition states to calculate the activation energy, Ea, of reactions (1) NO + O3 and (2) NO2 + O3 using the MP2 level of theory with three different basis sets and fine potential energy scan resolution.